KARAKTERISTIK FISIKO-KIMIA TEPUNG PRA-TREATMENT PISANG TANDUK UNTUK PENDERITA DIABETES MELITUS TIPE 2 - Palupi, Fitria Dhenok; Hapsari, Indri; Hasan Wattiheluw, Muhammad (Politeknik Kesehatan Kemenkes Bengkulu, 2024)
ABSTRACT The number of type 2 diabetes mellitus patients continues to rise annually, one of the contributing factors being dietary changes that affect gut microbiota. Glycemic control is a primary goal in diabetes management, which can be achieved through the intake of dietary fiber such as resistant starch that functions as a prebiotic. Tanduk bananas are a source of resistant starch, and their content can be enhanced through modifications such as pre-treatment involving heating and rapid cooling. This study aims to analyze the effects of combined pre-treatments, such as boiling, steaming, and storage at low temperatures (refrigerator and freezer), on the physicochemical quality of flour from local Indonesian tanduk bananas.The study involved 11 treatments with 3 replications, totaling 33 samples. The evaluated parameters included organoleptic properties, physical quality (bulk density and yield), and chemical quality (starch and resistant starch content). The results indicated that pre-treatment affected the color and texture of the banana flour, with steaming + freezer treatment influencing texture. This treatment significantly impacted physical quality and resistant starch content, but not starch content. The highest yield was found in boiling + freezer treatments for 24 and 48 hours, while the highest bulk density was observed in boiling, steaming, and refrigerator storage treatments. Resistant starch content increased with steaming + 48-hour freezer and boiling + 24-hour freezer treatments. In conclusion, the best treatments were boiling stored at 24-hour freezer and steaming stored at 48-hour freezer. Keywords: Type 2 Diabetes Mellitus; Tanduk Banana; Pre-treatment.